Neuroleptic Malignant Syndrome (NMS) on Clozapine with a Potential Atypical Interaction with Paliperidone - Paras Agarwal; Adanegbe Omoruyi; Kiara Gascon Perai; Kerenza MacDaid; Andrea Burton (Case Reports in Psychiatry)
Neuroleptic Malignant Syndrome (NMS) associated with the use of first-generation antipsychotics is a widely known phenomenon. This idiosyncratic reaction is less significant with the use of second-generation antipsychotics, and only a few cases in the literature exist, describing this reaction with clozapine use. While being titrated on clozapine, the patient developed major and minor criteria features of NMS as per the Diagnostic and Statistical Manual of Mental Disorders, Fifth edition (DSM-5) criteria except for fever, a core symptom which created diagnostic uncertainty. Initially, clozapine was temporarily discontinued due to his deteriorating mental and physical state. A rechallenge was considered at a much lower dose, but due to a rapid increase in his creatinine kinase (CK) levels within a 12-hour timeframe, clozapine was permanently stopped. The evidence further suggests that the presentation of NMS for patients on this medication may be different to the classical presentation, and other criteria for diagnosis are suggested, which may lower the threshold for investigating NMS for patients on clozapine.